ANALISIS MODEL PEMBELAJARAN BERBASIS LINGKUNGAN TERHADAP KEMAMPUAN KOGNITIF ANAK USIA 5-6 TAHUN DI RA MIFTAHUL ULUM KETANGI - Dwi Ayu Wulandari; Indriana Warih Indasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study emerged from the recognition that cognitive skills represent a central component of early childhood development, particularly for children aged 5-6 who are experiencing a crucial developmental window. In practice, however, learning activities in many early childhood education settings still follow conventional routines and have not fully utilized the surrounding environment as a meaningful learning resource capable of offering direct, concrete experiences. Responding to this gap, the present research seeks to examine differences in children’s cognitive performance before and after the implementation of an environment-based learning model, as well as to assess the effectiveness of this approach in fostering cognitive growth. A descriptive qualitative method within an experimental design framework was employed. The participants consisted of 30 children in Group B at RA Miftahul Ulum Ketangi, who were assigned to an experimental group and a control group. Data were collected through observation, testing, and documentation, and subsequently analyzed through data reduction, data display, and conclusion drawing, complemented by the nonparametric Mann Whitney U statistical test. The findings revealed a notable enhancement in the cognitive abilities of the experimental group, which obtained an average score of 2.87, in contrast to the control group’s mean score of 2.27. The significance value of 0.017 further demonstrated a statistically meaningful difference between the two groups. These results strongly suggest that environment based learning effectively strengthens children’s logical reasoning, problem-solving capacities, and symbolic thinking by engaging them in direct, contextual learning experiences. Overall, the environment based learning model has shown a substantial and positive influence on early childhood cognitive development.